AUTONOMY AND ITS IMPACT ON PRINCIPAL PERFORMANCE: A STUDY OF HIGHER SECONDARY SCHOOLS IN KASHMIR (International Journal of Food and Nutritional Sciences, 2022)
This study investigates the impact of autonomy on the performance of higher secondary school principals in Kashmir, a region characterized by political instability and socio-economic challenges. Using a quantitative approach, the research surveyed 60 principals to evaluate how varying levels of autonomy influence their leadership effectiveness and ability to manage school challenges. The findings reveal a significant positive correlation between higher autonomy and improved principal performance. Principals with high autonomy reported greater effectiveness in handling school-related issues and exhibited transformational leadership styles, whereas those with low autonomy faced more substantial challenges and tended to adopt less proactive leadership styles. The study highlights that increased decision-making freedom allows principals to address specific needs more effectively, suggesting that enhancing autonomy could lead to better educational outcomes. The results provide valuable insights for policymakers and educational authorities, advocating for policies that empower principals with greater autonomy to improve school management and performance in conflict-affected regions like Kashmir